Influence of Impurities in Electrical Contacts on Increasing the Efficiency of Energy Transmission - Dušan Medveď; Ľubomír Beňa; Michal Kolcun; Marek Pavlík (Energies, 2022)
The aim of this paper is to analyze the heat distribution in the high-current electrical contact under the action of an assumed current of 3000 A using mathematical modeling and simulation. Electrical contacts that carry high currents are an essential component of many electric devices. In transmission and distribution systems, the electrical contacts are of particular importance because they must withstand adverse weather conditions that decrease their effectiveness. Therefore, it is essential to detect any rise in temperature of the electrical contact to ensure efficient and reliable energy transmission. For this paper, simulations of the temperature field in direct electrical contact were carried out in ANSYS and discussed. During the simulation, a high-current electric contact was exposed to 3000 A current and the change of the adverse effects of contaminated contact layers affected temperature field. According to the results, electric contact in good condition (represented by impurity layer of lower resistivity) had a temperature of 80 °C lower than an electric contact that was worn out (represented by impurity layer of higher resistivity). The investigation of the resistivity of contaminated contact layers has led to the determination of permissible values for the power grid operators to maintain these types of devices when temperatures rise.